School holidays - Wells, Leanne (Cambridge University Press, 2002)
Bright Sparks Literacy Project is a set of reading materials that provide staged opportunities for children to learn to read in the early years of schooling. Each title draws on a broad base of literacy skills so that teachers can select texts according to students' needs